Preference and infestation level of Anastrepha fraterculus (Wiedemann, 1830) on fruits of some Psidium guajava L. cultivars and relation to their physicochemical parameters - Oliveira, Flavia Q. de [UNESP]; Boica Junior, Arlindo L. [UNESP]; Costa, Maria de Lourdes Z.; Sanches, Patricia A.; Walder, Julio M. M.; Batista, Jacinto de L. (Springer, 2014)
This study aimed to verify the preference and infestation level of Anastrepha fraterculus (Diptera: Tephritidae) [South American fruit fly] in fruits of guava cultivars and to correlate them to variables such as peel coloration, soluble solids and pH of fruit cultivars. The following cultivars were used: Pedro Sato, Paluma, Casco and S,culo XXI. The infestation was evaluated in cages, considering two scenarios: no-choice and multiple choice. In both tests, evaluations of the fruit attraction to insects were conducted for a period of 1', 3', 5', 10', 20', 30', 1 h, 2 h, 6 h, 12 h and 24 h. The visit of A. fraterculus on the assayed cultivars in relation to the time was studied by logistic regression. After 10 days, the number of larvae in each fruit was recorded. In the multiple choice test, the visit proportions were significantly higher in the fruits of cvs. S,culo XXI and Pedro Sato than in those of cvs. Paluma and Casco. In the no-choice test, the visit proportions were significantly lower in the Paluma fruits. In both tests, the rate of fruit infestation by A. fraterculus did not differ among cvs. Pedro Sato, Paluma and Casco, whereas the fruits of cv. S,culo XXI were more infested. The indexes of pH did not interfere with the infestation of A. fraterculus, whereas a high rate of soluble solids and low color angle appear to be crucial for discriminating the fruits of the most susceptible cultivars. Infestation rate of S,culo XXI fruits displayed significant correlations with: A degrees Brix (r= 0.7078) and color angle (h) (r= -0.9499) of guava fruits under the multiple choice conditions.
Keywords: Fruit fly; Guava; Plant resistance to insects; Reproductive behavior; South American fruit fly; Tephritidae